Caracteres - Teofrasto (Classica Digitalia: Autores Gregos e Latinos: textos, 2014)
This publication includes the translation of the Characters of Theophrastus, with an introduction and footnotes, following the recent edition and commentary by J. Diggle. In the introduction, after a short information about the author and his intellectual activity, the different literary genres are considered that left their influence on this production by Theophrastus: the ethic thought of Aristotle, contemporary rhetoric and New Comedy. The study is complemented with an actualized bibliography.